2015
DOI: 10.1186/s13071-015-1030-z
|View full text |Cite
|
Sign up to set email alerts
|

Study of the snail intermediate hosts of urogenital schistosomiasis in Niakhar, region of Fatick, West central Senegal

Abstract: BackgroundSchistosoma haematobium is the most widespread schistosome species in Senegal and occurs in several regions of the country especially in the Sudan-Sahelian zone. The aims of the study were i) to determine the freshwater species ii) to ascertain the role of the identified snail species in the transmission of S. haematobium and iii) to study the impact of drought on the snails.MethodsSnails were sampled each year in 17 sites from July to November-December 2012 and 2013. At each snail survey, snails wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
70
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(82 citation statements)
references
References 14 publications
11
70
1
Order By: Relevance
“…It was further posited that individual Bulinus species, ranging between 7-9.9 mm in size, were present in the month of July; 63.6% and 57.8% for B. senegalensis and B. umbilicatus, respectively. For the first time, this study reported that B. umbilicatus can maintain Schistosoma larvae for as long as seven months of drought, thereby resulting in the transmission of schistosomiasis in early July leading to an increased risk of schistosomiasis transmission in the study area [15]. Therefore, it is safe to deduce that prolonged drought periods for more than nine months can stop the transmission of schistosomiasis at the foci, while drought periods lasting less than seven months can aid the transmission of the disease in other parts of the region due to maintenance of the larval stage.…”
Section: Effect Of Drought On the Intermediate Host In Schistosomiasimentioning
confidence: 85%
See 4 more Smart Citations
“…It was further posited that individual Bulinus species, ranging between 7-9.9 mm in size, were present in the month of July; 63.6% and 57.8% for B. senegalensis and B. umbilicatus, respectively. For the first time, this study reported that B. umbilicatus can maintain Schistosoma larvae for as long as seven months of drought, thereby resulting in the transmission of schistosomiasis in early July leading to an increased risk of schistosomiasis transmission in the study area [15]. Therefore, it is safe to deduce that prolonged drought periods for more than nine months can stop the transmission of schistosomiasis at the foci, while drought periods lasting less than seven months can aid the transmission of the disease in other parts of the region due to maintenance of the larval stage.…”
Section: Effect Of Drought On the Intermediate Host In Schistosomiasimentioning
confidence: 85%
“…Studies have shown that during aestivation, uninfected Bulinus snail species have the ability to withstand longer periods of drought than infected snails [56,57,82]. This implies that during drought, infected snails die off and this alters the transmission of schistosomiasis in drought-stricken areas [15,56,57,82]. Mutuku and co-workers [56] analyzed temporal changes on the spatial transmission pattern of S. haematobium worms on different age groups and their relationship to ponds infested with Bulinus snails in coastal Kenya.…”
Section: Effect Of Drought On the Intermediate Host In Schistosomiasimentioning
confidence: 99%
See 3 more Smart Citations